Integrating negative dependencies assessment during mechatronics conceptual design using fuzzy logic and quantitative graph theory. (May 2019) - Chouinard, Ugo; Achiche, Sofiane; Baron, Luc
Abstract: This paper introduces a product-related dependency index that can be used during the conceptual design of mechatronic systems. The index uses fuzzy assessment of adverse effects dependencies combined with quantitative graph theory to compute the level of detrimental interactions present in a system. The paper also illustrates how the assessment of dependencies can be performed during early design stages and how components are differently affected by a specific adverse effect. Furthermore, the practicality of the new dependency index is exemplified with two case studies: a design experiment on a self-balancing robot and the conceptual design of a robotic arm for aerial manipulation. The design experiment demonstrates how adverse effects affect the performance of a mechatronic system and how the new dependency index is able to follow the decrease or increase of performance of the system. Then, the design of the robotic arm shows that decision-making can be improved when using this new dependency index as a criterion, as it allows one to select concepts for which less detrimental interactions exist. In both case studies, the index is shown to facilitate the design process as it can lead to fewer redesign loops which would result in reducing the development time and costs.